Lead-free energy storage ceramic laminated material and preparation method thereof

By using the stacked structure design of non-textured ceramics and textured ceramics in energy storage ceramic materials, the problem that existing ceramic materials are difficult to have high polarization strength and breakdown electric field strength is solved, and ceramic materials with high energy storage density are realized, suitable for high power electronics and pulse power fields.

CN119590051APending Publication Date: 2025-03-11NANJING UNIV OF AERONAUTICS & ASTRONAUTICS
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411728843.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

It is difficult for existing energy storage ceramic materials to have high polarization strength and high breakdown electric field strength, which limits their energy storage density and application potential.

Method used

Non-textured ceramics are used as high-pressure resistance layer and textured ceramics are used as high-polarization layers to prepare lead-free energy-storage ceramic materials through stacked structure design, and the polarization strength and breakdown field strength are synergistically improved by the interface barrier effect.

Benefits of technology

The coordinated improvement of high polarization strength and high breakdown field strength has been achieved, and the energy storage density has been significantly improved, which is suitable for high-power electronics and pulse power fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119590051A_ABST
    Figure CN119590051A_ABST
Patent Text Reader

Abstract

The invention discloses a lead-free energy storage ceramic laminated material, and belongs to the technical field of dielectric energy storage. The lead-free energy storage ceramic laminated material is formed by sequentially laminating lead-free energy storage ceramic with a texture structure and lead-free energy storage ceramic with a non-texture structure, and preferably, the material comprises at least three layers; when the lead-free energy storage ceramic with the texture structure is positioned on the middle layer, the lead-free energy storage ceramic with the non-texture structure is positioned on the two sides of the middle layer; when the lead-free energy storage ceramic with the non-texture structure is located on the middle layer, the lead-free energy storage ceramic with the texture structure is located on the two sides of the middle layer. Based on the structural design of at least three layers, the non-textured ceramic is selected as the high-voltage-resistant layer, the textured ceramic is selected as the high-polarization layer, the lead-free ceramic laminated material with excellent energy storage performance is obtained, and the lead-free ceramic laminated material has wide application prospects in the fields of power electronics and pulse power.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of dielectric energy storage, and in particular to a lead-free energy storage ceramic laminate material and a preparation method thereof. Background Art

[0002] With the rapid development of economy and technology, human demand for energy is increasing. At present, there are three main types of electrical energy storage devices: batteries, electrochemical capacitors and dielectric capacitors. Among them, the energy storage principle of dielectric capacitors is that the internal dipoles are polarized and deflected under the action of the electric field, generating polarized charges to realize the charging and discharging process. There is no material transfer and redox process in the whole process, so the charging and discharging speed is extremely fast. Specifically, it has an ultra-high power density (10 6 -10 7 W / kg) and microsecond or even nanosecond charge and discharge rates. Coupled with its simple structure, all-solid components, and good environmental adaptability, it plays an irreplaceable and key role in the fields of electric vehicles, smart grids, high-power devices, and advanced weapons and equipment, and plays an important role in the national economy and major national strategic needs.

[0003] The only drawback is that the releasable energy storage density of dielectric capacitors is lower than that of energy storage devices such as batteries and electrochemical capacitors. This not only severely limits its practical application, but also goes against the trend of miniaturization and integration of energy storage devices. In order to improve the releasable energy storage density, it is necessary to simultaneously improve the polarization strength and breakdown field strength. Ceramics have the characteristics of high dielectric constant (favorable to high polarization strength), excellent high-temperature service performance, low dielectric loss and large charge and discharge rate, and play a pivotal role in the dielectric capacitor material system. Looking at the four types of ceramic dielectric materials, linear dielectric ceramics, ferroelectric ceramics, relaxor ferroelectric ceramics and antiferroelectric ceramics, antiferroelectric ceramics have no intrinsic domain wall movement, and there is no obvious hysteresis effect before the antiferroelectric-ferroelectric (AFE-FE) phase transition occurs, so the dielectric loss is small under low electric fields; under high electric fields, the antiparallel arranged dipoles will form a ferroelectric order arranged in the same direction, thereby showing a large polarization change, and finally showing a considerable energy storage density.

[0004] The most widely studied antiferroelectric ceramics include PbZrO 3 、AgNbO 3 ,NaNbO 3 、(Na,Bi)TiO 3Etc. Considering the harmfulness of lead-containing systems to the human body and the environment, the current research direction is to vigorously develop lead-free green ceramic materials. Niobate systems (such as silver niobate, sodium niobate, etc.) will undergo a series of structural phase transitions when the temperature changes, providing a broad space for the regulation of dielectric energy storage performance. Take sodium niobate ceramics as an example: when the temperature drops from a high temperature of more than 600°C to -100°C, sodium niobate ceramics exhibit paraelectricity, antiferroelectricity and ferroelectricity in turn. It is particularly worth mentioning that sodium niobate is an antiferroelectric phase at room temperature, which provides a basis for a higher releasable energy storage density. In addition, its raw materials are sufficient and low-cost, and the preparation process does not require a protective atmosphere, which has attracted widespread attention from researchers in recent years.

[0005] Generally speaking, high maximum polarization intensity and excellent breakdown strength are the key to obtaining excellent energy storage performance. However, in general single-phase dielectric materials, the two are intrinsically anti-correlated and difficult to significantly improve at the same time. This is because: high polarization intensity will bring a strong dipole field, resulting in a larger local electric field. The local electric field tends to distort or weaken polar molecular bonds, making them easier to break, so that the dielectric material exhibits a lower breakdown strength (J.Liu et.al, J.Appl.Phys., 2019, 125,115103; JWMcPherson et.al, J.Appl.Phys., 2000, 88,5351). The anti-correlation between the maximum polarization intensity and breakdown strength of single-phase dielectric materials leads to insufficient energy storage density, limiting its application in high-power energy storage devices.

[0006] Utilizing the composite effect of "1+1>2" is an effective method to synergistically improve the maximum polarization strength and breakdown strength of dielectric materials, that is, compounding material A with excellent maximum polarization strength with material B with high breakdown strength. Materials A and B provide high maximum polarization strength and strong breakdown field strength, respectively, and ultimately optimize the energy storage density of the composite material. Different from the 0-3, 1-3, 2-2 and other composite forms commonly used in polymer-based composite dielectric materials, the composite of ceramic materials generally adopts a 2-2 laminated form. So far, some literature has reported that excellent energy storage performance was finally achieved by laminating a ceramic layer with high polarization strength and another ceramic layer with high breakdown strength (F. Yan et. al, Small, 2024, 20, 2306803; F. Yan et. al, J. Mater. Chem. A, 2020, 8, 11656; F. Yan et. al, J. Mater. Chem. A, 2021, 9, 15827). However, when two or more materials are used for lamination, there are inevitably problems of co-firing mismatch during the sintering process, such as: (1) the optimal sintering temperature and process of different materials are inconsistent, and the optimal performance of various materials cannot be achieved after co-firing; (2) the thermal expansion coefficient does not match, resulting in sintering shrinkage, deformation and residual stress; (3) interface reaction and / or element diffusion between different materials. These problems must be considered during the co-firing process, and can only be effectively controlled and solved through continuous process improvement. Exploring the co-firing process takes a long time, which greatly prolongs the cycle of developing laminated ceramics.

[0007] Based on this, it is urgent to explore a new type of energy storage ceramic material that can take into account both maximum polarization intensity and breakdown electric field. Summary of the invention

[0008] In view of the problem that general energy storage ceramics in the prior art cannot have both high polarization strength and high breakdown electric field strength, the present invention discloses a lead-free energy storage ceramic laminate material and a preparation method thereof. The present invention is based on a structural design of at least three layers, selects non-textured ceramics as a high voltage resistance layer and textured ceramics as a high polarization layer, and obtains a lead-free ceramic laminate material with excellent energy storage performance, which has broad application prospects in the fields of power electronics and pulse power.

[0009] The technical solution of the present invention is as follows:

[0010] A lead-free energy storage ceramic laminated material is formed by sequentially stacking a lead-free energy storage ceramic with a textured structure and a lead-free energy storage ceramic with a non-textured structure.

[0011] Preferably, the material includes at least three layers; when the lead-free energy storage ceramic with a textured structure is located in the middle layer, its two sides are lead-free energy storage ceramics with a non-textured structure; when the lead-free energy storage ceramic with a non-textured structure is located in the middle layer, its two sides are lead-free energy storage ceramics with a textured structure.

[0012] Preferably, the lead-free energy storage ceramics include niobate-based, barium titanate-based, sodium bismuth titanate-based, and bismuth ferrite-based perovskite ceramics.

[0013] More preferably, the niobate-based perovskite ceramic includes sodium niobate, potassium niobate, lithium niobate, silver niobate, and potassium sodium niobate.

[0014] The present invention also provides a method for preparing the lead-free energy storage ceramic laminate material, comprising the following steps:

[0015] S1. Take carbonates or oxides of each element in the chemical formula of the lead-free energy storage ceramic and prepare ingredients according to the molar ratio of each element in the chemical formula;

[0016] S2, subjecting the prepared raw materials to primary pulverizing ball milling, pre-calcination, secondary pulverizing ball milling or no secondary pulverizing ball milling, drying and sieving in sequence to obtain a basic powder;

[0017] S3, mixing the base powder with a solvent, a dispersant, a plasticizer, and a binder to obtain a non-textured ceramic tape-casting slurry; mixing the base powder with a solvent, a dispersant, a plasticizer, a binder, and a template to obtain a textured ceramic tape-casting slurry;

[0018] S4. The textured ceramic casting slurry and the non-textured ceramic casting slurry are respectively cast to obtain textured green ceramic sheets and non-textured green ceramic sheets, and the textured green ceramic sheets and non-textured green ceramic sheets are stacked in this order to obtain a ceramic green embryo, and then the binder is removed and sintered to obtain the lead-free energy storage ceramic laminate material.

[0019] Furthermore, in step S1, the purity of the carbonate or oxide of each element is not less than 99%.

[0020] If there is a Na element in the chemical formula, select its corresponding Na 2 CO 3 or NaHCO 3 ;

[0021] If K element exists in the chemical formula, select its corresponding KHCO 3 or K 2 CO 3 ;

[0022] If there is a Li element in the chemical formula, select its corresponding Li 2 CO 3 ;

[0023] If there is Nb element in the chemical formula, select its corresponding Nb 2 O 5 ;

[0024] If there is Bi element in the chemical formula, select its corresponding Bi 2 O 3 ;

[0025] If there is Fe in the chemical formula, select the corresponding Fe 2 O 3 ;

[0026] If there is a Ta element in the chemical formula, select its corresponding Ta 2 O 5 ;

[0027] If there is an Sb element in the chemical formula, select the corresponding Sb 2 O 5 ;

[0028] If there is Zr in the chemical formula, select its corresponding ZrO 2 ;

[0029] If there is an Sr element in the chemical formula, select its corresponding SrCO 3 ;

[0030] If there is an Ag element in the chemical formula, select its corresponding Ag 2 O;

[0031] If there is Mg in the chemical formula, select its corresponding MgO or MgCO 3 ;

[0032] If there is an Hf element in the chemical formula, select its corresponding HfO 2 ;

[0033] And so on.

[0034] For example, when the chemical formula of the niobate ceramic is 0.85NaNbO 3 -0.15BiFeO 3 When the final 20g of 0.85NaNbO 3 -0.15BiFeO 3 For example, 4.3882 g of Na 2 CO 3 (purity 99.8%), 11.0382g Nb 2 O 5 (purity 99.5%), 3.4180g of Bi2 O 3 (Excess 0.5wt%, purity 99.9%), 1.1726g mass of Fe 2 O 3 (purity 99.0%), and the purity of the above raw materials is not less than 99%.

[0035] Preferably, in step S2, the ball milling medium for the primary pulverizing ball mill and the secondary pulverizing ball mill is anhydrous ethanol, and the ball milling speed is 250-350 r / min respectively; wherein the time for the primary pulverizing ball mill is 8-14 h, and the time for the secondary pulverizing ball mill is 16-26 h;

[0036] The pre-calcination is to increase the temperature to 750-950°C at 1-5°C / min and keep the temperature for 2.5-4h;

[0037] The drying and screening is to dry the powder after the secondary powder making ball milling at a temperature of 75-85° C. and pass it through a 80-200 mesh sieve.

[0038] Preferably, in step S3, the solvent is one or both of anhydrous ethanol and butanone; the dispersant is KD1, the plasticizer is dibutyl phthalate, the binder is polyvinyl butyral, and the template is NaNbO 3 Flake microcrystal template.

[0039] Preferably, in step S3, when preparing the textured ceramic tape casting slurry and the non-textured ceramic tape casting slurry, the solvent accounts for 140-160wt% of the respective base powders, the dispersant accounts for 1.8-2.2wt% of the respective base powders, the plasticizer accounts for 5.8-6.2wt% of the respective base powders, and the binder accounts for 4.8-5.2wt% of the respective base powders;

[0040] When preparing textured ceramic tape casting slurry, the template accounts for 4-5wt% of the basic powder.

[0041] Furthermore, the solvent in step S3 can be a mixture of anhydrous ethanol and butanone, wherein the anhydrous ethanol accounts for 43-48wt% of the basic powder, and the butanone accounts for 97-112wt% of the basic powder.

[0042] Furthermore, in the process of preparing the non-textured ceramic slurry in step S3, the base powder is first mixed with the solvent and the dispersant, and ball-milled at 250-350 r / min for 20-30 hours for the first pulping ball milling, and then the plasticizer and the binder are added, and the ball milling is continued at 250-350 r / min for 10-15 hours for the second pulping ball milling; in addition to the above steps, the process of preparing the textured ceramic slurry further includes adding the template and continuing to stir for 0.5-2 hours.

[0043] Preferably, in step S4, when the lamination is three layers, the lamination method is to sandwich the textured green ceramic sheet between the non-textured green ceramic sheets, and maintain the pressure at 4-8 MPa for 30-60 min to obtain a ceramic green embryo; or sandwich the non-textured green ceramic sheet between the textured green ceramic sheets, and maintain the pressure at 4-8 MPa for 30-60 min to obtain a ceramic green embryo.

[0044] Preferably, in step S4, the debinding process parameters are: debinding temperature 620-700°C, holding time 4-6h; the sintering process parameters are: sintering temperature 1095-1240°C, holding time 3-4.5h.

[0045] Furthermore, in step S4, before the slurry is cast, the slurry is first degassed in a vacuum machine for 10-30 minutes.

[0046] Furthermore, the heating rate of the debinding process in step S4 is 1-5°C / min, and the heating rate of the sintering is 1-5°C / min. The sintering can be carried out by embedding powder, and the embedded powder is a pre-fired ceramic powder with the same general formula as the ceramic, wherein the pre-fired temperature is 750-950°C.

[0047] The beneficial technical effects of the present invention are:

[0048] 1. The present invention uses non-textured ceramics as the high voltage-resistant layer and textured ceramics as the high polarization layer to prepare laminated energy storage ceramics, which overcomes the problem that lead-free single-phase energy storage ceramics, especially niobate-based energy storage ceramics (such as sodium niobate, potassium niobate, silver niobate, etc.), cannot have both high polarization strength and high breakdown electric field strength. Moreover, the lamination of textured and non-textured ceramics of the same material system effectively avoids the co-firing mismatch problem in the lamination process of two or more materials, reduces the difficulty of sintering process exploration and shortens the development cycle. Taking the sodium niobate system as an example, the technical effect of the present invention achieves a maximum polarization strength of 47.4μC / cm for the sandwich structure. 2 , breakdown field strength 728kV / cm, can release energy storage density up to 11.9J / cm 3 Excellent performance.

[0049] 2. Generally speaking, textured ceramics have higher temperature stability and frequency stability, while non-textured ceramics have better isotropy in electrical and mechanical properties. However, the inventors discovered during the experiment that these two structures have other unexpected properties when superimposed.

[0050] Specifically, in the laminated ceramics of the present invention, ceramic layers with different dielectric constants redistribute the electric field, and the low dielectric constant dielectric layer shares the high electric field; since the dielectric constant of the non-textured ceramic is relatively small compared to the corresponding textured ceramic, the electric field is concentrated in the non-textured ceramic layer with a relatively low dielectric constant, so that the non-textured layer in the laminate exhibits a higher breakdown strength than the non-textured ceramic without the laminate, which indicates that an interface blocking effect is generated in the laminate structure, which can effectively inhibit the expansion of the electric tree in the entire laminated ceramic. At the same time, the textured ceramic layer has a specific crystal orientation, which is conducive to the arrangement and polarization of the electric domain, and can more effectively respond to the external electric field, so that the textured ceramic layer obtains a large polarization strength, and finally makes the non-textured and textured laminated ceramics have excellent comprehensive energy storage performance compared to the corresponding single-phase block non-textured ceramics or textured ceramics.

[0051] The present invention stacks a textured ceramic layer with a non-textured ceramic to give full play to the advantages of high polarization strength and large breakdown field strength through a synergistic effect, thereby overcoming the problem of anti-correlation between the breakdown electric field and the polarization strength in general single-phase materials.

[0052] 3. Compared with ceramic laminated materials with different chemical compositions, each layer of ceramic in the lead-free energy storage ceramic laminated material of the present invention has the same chemical composition. After the tape-cast green ceramic tape is laminated, it is easy to co-fire the multi-layer structure, which effectively avoids the problems of inconsistent co-firing process, mismatched thermal expansion coefficients, interface reactions between different materials and / or element interdiffusion when co-firing different materials, reduces the difficulty of preparation, and effectively shortens the development cycle. The strategy of using non-textured ceramics as high-voltage-resistant layers and textured ceramics as high-polarization layers to prepare laminated energy storage ceramics can also be extended to other material systems, such as silver niobate systems.

[0053] 4. Compared with ordinary non-textured energy storage ceramics or fully textured energy storage ceramics, the laminated material of the present invention can release energy storage density and efficiency increased by 29.35% and 3.23%. In addition, in the present invention, the raw materials used do not contain lead components, so it is environmentally friendly and will not cause pollution. BRIEF DESCRIPTION OF THE DRAWINGS

[0054] Figure 1 1 and 2 are XRD patterns of the laminated ceramics prepared in Examples 1 and 2 and Comparative Examples 1 and 2, wherein S1 is Comparative Example 1, S2 is Example 1, S3 is Example 2, and S4 is Comparative Example 2. Figure 2-Figure 5 The symbols represent the same meaning;

[0055] Figure 2 is the Weber breakdown diagram of the laminated ceramics prepared in Examples 1 and 2 and Comparative Examples 1 and 2;

[0056] Figure 3500 kV / cm hysteresis loop diagram of the multilayer ceramics prepared in Examples 1 and 2 and Comparative Examples 1 and 2;

[0057] Figure 4 hysteresis loop diagrams of the multilayer ceramics prepared in Examples 1 and 2 and Comparative Examples 1 and 2 under near-maximum electric fields;

[0058] Figure 5 is a comparison chart of the energy storage performance of the laminated ceramics prepared in Examples 1 and 2 and Comparative Examples 1 and 2;

[0059] Figure 6 : are XRD patterns of the laminated ceramics prepared in Examples 3 and 4 and Comparative Examples 3 and 4, wherein S1 is Comparative Example 3, S2 is Example 3, S3 is Example 4, and S4 is Comparative Example 4. Figure 7-Figure 9 The symbols represent the same meaning;

[0060] Figure 7 is the Weber breakdown diagram of the laminated ceramics prepared in Examples 3 and 4 and Comparative Examples 3 and 4;

[0061] Figure 8 1 is a hysteresis loop diagram of the multilayer ceramics prepared in Examples 3 and 4 and Comparative Examples 3 and 4;

[0062] Fig. 9 is a comparison chart of the energy storage performance of the laminated ceramics prepared in Examples 3 and 4 and Comparative Examples 3 and 4;

[0063] Fig.10 : are XRD patterns of the laminated ceramics prepared in Examples 5 and 6 and Comparative Examples 5 and 6, wherein S1 is Comparative Example 5, S2 is Example 5, S3 is Example 6, and S4 is Comparative Example 6. Figure 11-13 The symbols represent the same meaning;

[0064] Fig.11 is the Weber breakdown diagram of the laminated ceramics prepared in Examples 5 and 6 and Comparative Examples 5 and 6;

[0065] Fig.12 1 is a hysteresis loop diagram of the multilayer ceramics prepared in Examples 5 and 6 and Comparative Examples 5 and 6;

[0066] Fig.13 It is a comparison chart of the energy storage performance of the multilayer ceramics prepared in Examples 5 and 6 and Comparative Examples 5 and 6. DETAILED DESCRIPTION

[0067] The present invention is described in detail below in conjunction with the accompanying drawings and embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0068] Embodiment 1:

[0069] This embodiment provides a lead-free energy storage ceramic laminate material. The lead-free energy storage ceramic is a sodium niobate-based ceramic with a general chemical formula of 0.85NaNbO 3 -0.15BiFeO 3 The preparation method is carried out according to the following steps:

[0070] (1) Take Na 2 CO 3 (99.8%), Nb 2 O 5 (99.5%), Bi 2 O 3 (99.9%) and Fe 2 O 3 (99.0%) as raw materials, according to the chemical formula 0.85NaNbO 3 -0.15BiFeO 3 The ingredients were mixed. Finally, 20 g of 0.85 NaNbO was synthesized. 3 -0.15BiFeO 3 Ceramic powder, select 4.3882g of Na 2 CO 3 , 11.0382 g of Nb 2 O 5 , 3.4180g of Bi 2 O 3 (0.5 wt% excess), 1.1726 g of Fe 2 O 3 .

[0071] The weighed raw materials were put into a ball mill and anhydrous ethanol was added as a ball milling medium, and the ball milling was carried out at a speed of 300r / min for 12 hours to carry out the first pulverizing ball milling; the raw materials after ball milling were dried, and the raw materials pressed into sheets were heated to 900℃ at 5℃ / min and kept warm for 3 hours, and then cooled with the furnace to complete pre-burning; the pre-burned powder was put into a ball mill and anhydrous ethanol was added as a ball milling medium, and the ball milling was carried out at a speed of 350r / min for 16 hours to carry out the second pulverizing ball milling; the powder after the second pulverizing ball milling was dried at 80℃ and passed through a 140-mesh sieve to obtain a basic powder.

[0072] (2) Weigh 10 g of the basic powder prepared in step (1) and put it into a 100 mL ball mill. Add 0.2 g of dispersant KD 1 (manufacturer: Heda Industrial, dispersant model: Hypermer KD 1, the same below), 10.5 g of butanone, and 4.5 g of anhydrous ethanol, respectively. Ball mill the mixture at a speed of 250 r / min for 30 h to perform a first pulping ball mill. After the ball milling process, directly add 0.58 g of dibutyl phthalate and 0.5 g of polyvinyl butyral into the ball mill. Continue ball milling at a speed of 350 r / min for 10 h to perform a second pulping ball mill.

[0073] (3) Pour the tape-casting slurry prepared in step (2) into a beaker. The tape-casting slurry for preparing the non-textured ceramic layer green tape is not added with a template. The tape-casting slurry for preparing the textured ceramic layer green tape is added with 0.5 g of <100> Oriented NaNbO 3 template and stirred magnetically for 2 h.

[0074] (4) The treated casting slurry is debubbled in a vacuum machine for about 20 minutes, and then the non-textured ceramic green sheets and textured ceramic layer green sheets are respectively prepared by the casting method, and the sheets are cut in turn (divided into squares with a side length of 15 mm). A piece of textured ceramic layer green sheet is placed between two pieces of non-textured ceramic layer green sheets for stacking, and the pressure is maintained at 8MPa for 30 minutes to obtain a laminated ceramic green embryo. The molded ceramic green embryo is heated to 660℃ at a heating rate of 1℃ / min and kept warm for 5 hours to complete the debinding. The ceramic green embryo after debinding is placed in a crucible for powder embedding treatment (the embedded powder is 0.85NaNbO pre-fired at 900℃ 3 -0.15BiFeO 3 The powder was heated to 1095°C at a rate of 5°C / min and kept for 4.5h to complete the sintering.

[0075] Comparative Example 1:

[0076] The difference between this comparative example and Example 1 is that: First, step (3) is omitted, and 0.5 g of ... <100> Oriented NaNbO 3 The template is magnetically stirred for 2 hours, and secondly, in step (4), only non-textured ceramic green sheets are used for lamination, and finally non-textured energy storage ceramics are obtained. Other steps and parameters are the same as those in Example 1.

[0077] Embodiment 2:

[0078] This embodiment provides a lead-free energy storage ceramic laminate material. The lead-free energy storage ceramic is a sodium niobate-based ceramic with a general chemical formula of 0.85NaNbO 3 -0.15BiFeO 3 The preparation method is carried out according to the following steps:

[0079] (1) Take Na 2 CO 3 (99.8%), Nb 2 O 5 (99.5%), Bi 2 O 3 (99.9%) and Fe 2 O 3 (99.0%) as raw materials, according to the chemical formula 0.85NaNbO 3 -0.15BiFeO 3 The ingredients were mixed and 20 g of 0.85 NaNbO was finally synthesized. 3 -0.15BiFeO 3 Ceramic powder, select 4.3882g of Na 2 CO 3 , 11.0382 g of Nb 2 O 5 , 3.4180g of Bi 2 O 3 (0.5 wt% excess), 1.1726 g of Fe 2 O 3 .

[0080] The weighed raw materials were put into a ball mill and anhydrous ethanol was added as a ball milling medium, and the ball milling was carried out at a speed of 300r / min for 12 hours to carry out the first pulverizing ball milling; the raw materials after ball milling were dried, and the raw materials pressed into sheets were heated to 900℃ at 5℃ / min and kept warm for 3 hours, and then cooled with the furnace to complete pre-burning; the pre-burned powder was put into a ball mill and anhydrous ethanol was added as a ball milling medium, and the ball milling was carried out at a speed of 350r / min for 16 hours to carry out the second pulverizing ball milling; the powder after the second pulverizing ball milling was dried at 80℃ and passed through a 140-mesh sieve to obtain a basic powder.

[0081] (2) Weigh 10 g of the basic powder prepared in step (1) and put it into a 100 mL ball mill. Add 0.2 g of dispersant KD1, 10.5 g of butanone, and 4.5 g of anhydrous ethanol respectively. Ball mill the mixture at a speed of 250 r / min for 30 h to perform a first pulping ball mill. After the ball milling process, directly add 0.58 g of dibutyl phthalate and 0.5 g of polyvinyl butyral into the ball mill. Continue ball milling at a speed of 350 r / min for 10 h to perform a second pulping ball mill.

[0082] (3) Pour the tape-casting slurry prepared in step (2) into a beaker. The tape-casting slurry for preparing the non-textured ceramic layer green tape is not added with a template. The tape-casting slurry for preparing the textured ceramic layer green tape is added with 0.5 g of <100> Oriented NaNbO 3 template and stirred magnetically for 2 h.

[0083] (4) The treated casting slurry is debubbled in a vacuum machine for about 20 minutes, and then the non-textured ceramic green sheets and textured ceramic layer green sheets are respectively prepared by the casting method, and the sheets are cut in turn (divided into squares with a side length of 15 mm). A non-textured ceramic layer green sheet is placed between two textured ceramic layer green sheets for stacking, and the pressure is maintained at 8MPa for 30 minutes to obtain a laminated ceramic green embryo. The molded ceramic green embryo is heated to 660℃ at a heating rate of 1℃ / min and kept warm for 5 hours to complete the debinding. The ceramic green embryo after debinding is placed in a crucible for powder embedding treatment (the embedded powder is 0.85NaNbO pre-fired at 900℃ 3 -0.15BiFeO 3 The powder was heated to 1095°C at a rate of 5°C / min and kept for 4.5h to complete the sintering.

[0084] Comparative Example 2:

[0085] The difference between this comparative example and Example 2 is that: first, in step (3), only the tape casting slurry of the textured ceramic layer green tape is prepared, and second, in step (4), only the textured ceramic green sheets are used for lamination to finally obtain the textured energy storage ceramic. The other steps and parameters are the same as those in Example 2.

[0086] Embodiment 3:

[0087] This embodiment provides a lead-free energy storage ceramic laminate material. The lead-free energy storage ceramic is a sodium niobate-based ceramic with a chemical formula of 0.88NaNbO 3 -0.12BiMg 0.5 Zr 0.5 O 3 The preparation method is carried out according to the following steps:

[0088] (1) Take Na 2 CO 3 (99.8%), Nb 2 O 5 (99.5%), Bi 2 O 3 (99.9%), MgO (99.99%), ZrO 2 (99.0%) as raw materials, according to the chemical formula 0.88NaNbO 3 -0.12BiMg 0.5 Zr 0.5 O 3 The ingredients were mixed and 20 g of 0.88 NaNbO was finally synthesized. 3 -0.12BiMg 0.5 Zr 0.5 O 3 Ceramic powder, select 4.6365g of Na 2 CO 3, 11.6058 g of Nb 2 O 5 , 2.7907 g of Bi 2 O 3 (excess 0.5wt%), 0.2400g MgO, 0.7410g ZrO 2 .

[0089] The weighed raw materials were put into a ball mill and anhydrous ethanol was added as a ball milling medium, and the ball milling was carried out at a speed of 250r / min for 14 hours to carry out the first pulverizing ball milling; the raw materials after ball milling were dried, and the raw materials pressed into sheets were heated to 950℃ at 3℃ / min and kept warm for 2.5 hours, and then cooled with the furnace to complete pre-burning; the pre-burned powder was put into a ball mill and anhydrous ethanol was added as a ball milling medium, and the ball milling was carried out at a speed of 300r / min for 20 hours to carry out the second pulverizing ball milling; the powder after the second pulverizing ball milling was dried at 85℃ and passed through an 80-mesh sieve to obtain a basic powder.

[0090] (2) Weigh 10 g of the basic powder prepared in step (1) and put it into a 100 mL ball mill. Add 0.22 g of dispersant KD1, 9.7 g of butanone, and 4.3 g of anhydrous ethanol respectively. Ball mill the mixture at 300 r / min for 25 h to perform a first slurry ball mill. After the ball milling process, directly add 0.62 g of dibutyl phthalate and 0.52 g of polyvinyl butyral into the ball mill. Continue ball milling at 250 r / min for 15 h to perform a second slurry ball mill.

[0091] (3) Pour the tape-casting slurry prepared in step (2) into a beaker. The tape-casting slurry for preparing the non-textured ceramic layer green tape is not added with a template. The tape-casting slurry for preparing the textured ceramic layer green tape is added with 0.4 g of <100> Oriented NaNbO 3 The template was stirred magnetically for 0.5 h.

[0092] (4) The treated casting slurry is debubbled in a vacuum machine for about 10 minutes, and then the non-textured ceramic green sheets and textured ceramic layer green sheets are respectively prepared by the casting method, and the sheets are cut in turn (divided into squares with a side length of 15 mm). A piece of textured ceramic layer green sheet is placed between two pieces of non-textured ceramic layer green sheets for stacking, and the pressure is maintained at 4 MPa for 60 minutes to obtain a laminated ceramic green embryo. The formed ceramic green embryo is heated to 700°C at a heating rate of 3°C / min and kept warm for 4 hours to complete the debinding. The ceramic green embryo after debinding is placed in a crucible for powder embedding treatment (the embedded powder is 0.88NaNbO pre-fired at 950°C) 3 -0.12BiMg 0.5 Zr 0.5 O 3 The powder was heated to 1240°C at a rate of 3°C / min and kept for 3 h to complete the sintering.

[0093] Comparative Example 3:

[0094] The difference between this comparative example and Example 3 is that: First, step (3) is omitted, and 0.4 g of <100> Oriented NaNbO 3 The template is magnetically stirred for 0.5h, and secondly, in step (4), only non-textured ceramic green sheets are used for lamination, and finally a traditional non-oriented energy storage ceramic is obtained. The other steps and parameters are the same as those in Example 3.

[0095] Embodiment 4:

[0096] This embodiment provides a lead-free energy storage ceramic laminate material. The lead-free energy storage ceramic is a sodium niobate-based ceramic with a chemical formula of 0.88NaNbO 3 -0.12BiMg 0.5 Zr 0.5 O 3 The preparation method is carried out according to the following steps:

[0097] (1) Take Na 2 CO 3 (99.8%), Nb 2 O 5 (99.5%), Bi 2 O 3 (99.9%), MgO (99.99%), ZrO 2 (99.0%) as raw materials, according to the chemical formula 0.88NaNbO 3 -0.12BiMg 0.5 Zr 0.5 O 3 The ingredients were mixed and 20 g of 0.88 NaNbO was finally synthesized. 3 -0.12BiMg 0.5 Zr 0.5 O 3 Ceramic powder, select 4.6365g of Na 2 CO 3 , 11.6058 g of Nb 2 O 5 , 2.7907 g of Bi 2 O 3 (excess 0.5wt%), 0.2400g MgO, 0.7410g ZrO 2 .

[0098] The weighed raw materials were put into a ball mill and anhydrous ethanol was added as a ball milling medium, and the ball milling was carried out at a speed of 250r / min for 14 hours to carry out the first pulverizing ball milling; the raw materials after ball milling were dried, and the raw materials pressed into sheets were heated to 950℃ at 3℃ / min and kept warm for 2.5 hours, and then cooled with the furnace to complete pre-burning; the pre-burned powder was put into a ball mill and anhydrous ethanol was added as a ball milling medium, and the ball milling was carried out at a speed of 300r / min for 20 hours to carry out the second pulverizing ball milling; the powder after the second pulverizing ball milling was dried at 85℃ and passed through an 80-mesh sieve to obtain a basic powder.

[0099] (2) Weigh 10 g of the basic powder prepared in step (1) and put it into a 100 mL ball mill. Add 0.22 g of dispersant KD1, 9.7 g of butanone, and 4.3 g of anhydrous ethanol respectively. Ball mill the mixture at 300 r / min for 25 h to perform a first slurry ball mill. After the ball milling process, directly add 0.62 g of dibutyl phthalate and 0.52 g of polyvinyl butyral into the ball mill. Continue ball milling at 250 r / min for 15 h to perform a second slurry ball mill.

[0100] (3) Pour the tape-casting slurry prepared in step (2) into a beaker. The tape-casting slurry for preparing the non-textured ceramic layer green tape is not added with a template. The tape-casting slurry for preparing the textured ceramic layer green tape is added with 0.4 g of <100> Oriented NaNbO 3 The template was stirred magnetically for 0.5 h.

[0101] (4) The treated casting slurry is debubbled in a vacuum machine for about 10 minutes, and then the non-textured ceramic green sheets and textured ceramic layer green sheets are respectively prepared by the casting method, and the sheets are cut in turn (divided into squares with a side length of 15 mm). A non-textured ceramic layer green sheet is placed between two textured ceramic layer green sheets for stacking, and the pressure is maintained at 4 MPa for 60 minutes to obtain a laminated ceramic green embryo. The formed ceramic green embryo is heated to 700°C at a heating rate of 3°C / min and kept warm for 4 hours to complete the debinding. The ceramic green embryo after debinding is placed in a crucible for powder embedding treatment (the embedded powder is 0.88NaNbO pre-fired at 950°C) 3 -0.12BiMg 0.5 Zr 0.5 O 3 The powder was heated to 1240°C at a rate of 3°C / min and kept for 3 h to complete the sintering.

[0102] Comparative Example 4:

[0103] The difference between this comparative example and Example 4 is that: first, in step (3), only the tape casting slurry of the textured ceramic layer green tape is prepared, and second, in step (4), only the textured ceramic green sheets are used for lamination to finally obtain the textured energy storage ceramic. The other steps and parameters are the same as those in Example 4.

[0104] Embodiment 5:

[0105] This embodiment provides a lead-free energy storage ceramic laminate material. The lead-free energy storage ceramic is a silver niobate-based ceramic with a general chemical formula of (Ag 0.71 Bi 0.07 Sr 0.04 )(Nb 0.85 Ta 0.15 ) 3 The preparation method is carried out according to the following steps:

[0106] (1) Pure AgNbO 3 , Nb 2 O 5 (99.5%), Ta 2 O 5 (99.99%), Bi 2 O 3 (99.999%) and SrCO 3 (99.95%) as raw materials, according to the chemical formula (Ag 0.71 Bi 0.07 Sr 0.04 )(Nb 0.85 Ta 0.15 ) 3 The ingredients were mixed and 14.3965 g of (Ag 0.71 Bi 0.07 Sr 0.04 )(Nb 0.85 Ta 0.15 ) 3 Ceramic powder, select 10.0000g of pure AgNbO 3 , 1.3356 g of Nb 2 O 5 , 1.9591g of Ta 2 O 5 , 1.1018 g of Bi 2 O 3 .

[0107] The weighed raw materials were placed in a ball mill and anhydrous ethanol was added as the ball milling medium, and the ball milling was performed at a speed of 350r / min for 8 hours to perform a powder-making ball milling. The raw materials after ball milling were dried, heated to 750℃ in oxygen at 1℃ / min, and then kept warm for 4 hours, and then cooled with the furnace to complete pre-burning. The pre-burned powder was sieved through a 200-mesh sieve to obtain a basic powder.

[0108] (2) Weigh 10 g of the basic powder prepared in step (1) and put it into a 100 mL ball mill. Add 0.18 g of dispersant KD1, 11.2 g of butanone, and 4.8 g of anhydrous ethanol respectively. Ball mill the mixture at 350 r / min for 20 h to perform a first slurry ball mill. After the ball milling process, directly add 0.6 g of dibutyl phthalate and 0.48 g of polyvinyl butyral into the ball mill. Continue ball milling at 300 r / min for 12 h to perform a second slurry ball mill.

[0109] (3) Pour the tape-casting slurry prepared in step (2) into a beaker, and do not add a template to prepare the tape-casting slurry for the non-textured ceramic layer green tape. Add 0.45 g of <100> Oriented NaNbO 3 template and stirred magnetically for 1 h.

[0110] (4) The treated casting slurry was debubbled in a vacuum machine for about 30 minutes, and then the non-textured ceramic green sheets and textured ceramic layer green sheets were respectively prepared by the casting method, and the sheets were cut in turn (divided into squares with a side length of 15 mm), and a textured ceramic layer green sheet was placed between two non-textured ceramic layer green sheets for stacking, and the pressure was maintained at 6MPa for 45 minutes to obtain a laminated ceramic green embryo, and the formed ceramic green embryo was heated to 620℃ in oxygen at a heating rate of 5℃ / min and kept warm for 6 hours to complete the debinding. The ceramic green embryo after debinding was placed in a crucible, and the temperature was raised to 1150℃ in oxygen at a heating rate of 1℃ / min and kept warm for 4 hours to complete the sintering.

[0111] Comparative Example 5:

[0112] The difference between this comparative example and Example 5 is that: First, step (3) is omitted, and 0.45 g of <100> Oriented NaNbO 3 The template is magnetically stirred for 1 hour. Second, in step (4), only non-textured ceramic green sheets are used for lamination to finally obtain non-textured energy storage ceramics. Other steps and parameters are the same as those in Example 5.

[0113] Embodiment 6:

[0114] This embodiment provides a lead-free energy storage ceramic laminate material. The lead-free energy storage ceramic is a silver niobate-based ceramic with a general chemical formula of (Ag 0.71 Bi 0.07 Sr 0.04 )(Nb 0.85 Ta 0.15 ) 3 The preparation method is carried out according to the following steps:

[0115] (1) Pure AgNbO 3 , Nb 2 O5 (99.5%), Ta 2 O 5 (99.99%), Bi 2 O 3 (99.999%) and SrCO 3 (99.95%) as raw materials, according to the chemical formula (Ag 0.71 Bi 0.07 Sr 0.04 )(Nb 0.85 Ta 0.15 ) 3 The ingredients were mixed and 14.3965 g of (Ag 0.71 Bi 0.07 Sr 0.04 )(Nb 0.85 Ta 0.15 ) 3 Ceramic powder, select 10.0000g of pure AgNbO 3 , 1.3356 g of Nb 2 O 5 , 1.9591g of Ta 2 O 5 , 1.1018 g of Bi 2 O 3 .

[0116] The weighed raw materials were placed in a ball mill and anhydrous ethanol was added as the ball milling medium, and the ball milling was performed at a speed of 350r / min for 8 hours to perform a powder-making ball milling. The raw materials after ball milling were dried, heated to 750℃ in oxygen at 1℃ / min, and then kept warm for 4 hours, and then cooled with the furnace to complete pre-burning. The pre-burned powder was sieved through a 200-mesh sieve to obtain a basic powder.

[0117] (2) Weigh 10 g of the basic powder prepared in step (1) and put it into a 100 mL ball mill. Add 0.18 g of dispersant KD1, 11.2 g of butanone, and 4.8 g of anhydrous ethanol respectively. Ball mill the mixture at 350 r / min for 20 h to perform a first slurry ball mill. After the ball milling process, directly add 0.6 g of dibutyl phthalate and 0.48 g of polyvinyl butyral into the ball mill. Continue ball milling at 300 r / min for 12 h to perform a second slurry ball mill.

[0118] (3) Pour the tape-casting slurry prepared in step (2) into a beaker, and do not add a template to prepare the tape-casting slurry for the non-textured ceramic layer green tape. Add 0.45 g of <100> Oriented NaNbO 3 template and stirred magnetically for 1 h.

[0119] (4) The treated casting slurry was debubbled in a vacuum machine for about 30 minutes, and then the non-textured ceramic green sheets and textured ceramic layer green sheets were respectively prepared by the casting method, and the sheets were cut in turn (divided into squares with a side length of 15 mm), and a non-textured ceramic layer green sheet was placed between two textured ceramic layer green sheets for stacking, and the pressure was maintained at 6MPa for 45 minutes to obtain a laminated ceramic green embryo, and the formed ceramic green embryo was heated to 620℃ in oxygen at a heating rate of 5℃ / min and kept warm for 6 hours to complete the debinding. The ceramic green embryo after debinding was placed in a crucible, and the temperature was raised to 1150℃ in oxygen at a heating rate of 1℃ / min and kept warm for 4 hours to complete the sintering.

[0120] Comparative Example 6:

[0121] The difference between this comparative example and Example 6 is that: first, in step (3), only the tape casting slurry of the textured ceramic layer green tape is prepared, and second, in step (4), only the textured ceramic green sheets are used for lamination to finally obtain the textured energy storage ceramic. The other steps and parameters are the same as those in Example 6.

[0122] Test example:

[0123] The lead-free energy storage ceramic materials obtained in Examples 1 and 2 and Comparative Examples 1 and 2 were analyzed: Figure 1 It can be seen that all samples show a typical perovskite structure, with the textures of S1, S2, S3 and S4 being 1.2%, 8.8%, 87.5% and 82.8% respectively. It should be noted that in some cases, the texture of the two-layer texture is higher than that of the three-layer texture. There may be two reasons for this: first, in general, too much template may inhibit the oriented growth of grains, resulting in a decrease in texture, which is why we limit the template to no more than 5wt% of the powder mass; second, the template may be unevenly distributed in the green porcelain belt, resulting in a deviation in orientation within a reasonable range. However, the size of the texture does not affect the energy storage properties after the texture and non-texture are stacked.

[0124] refer to Figure 2 , Figure 3 It can be seen that the non-textured ceramic S1 has a higher breakdown strength than the textured ceramic and a lower polarization strength under the same electric field; while the textured ceramic S4 has the opposite characteristics to the non-textured ceramic S1, that is, the textured ceramic S4 has a lower breakdown strength than the non-textured ceramic and a higher polarization strength under the same electric field. Figure 4 , Figure 5 It can be seen that based on the three-layer structure design, the laminated ceramic S2 prepared by selecting non-textured ceramic as the high voltage-resistant layer and the textured ceramic sandwiched between the non-textured ceramic as the high polarization layer has achieved a maximum polarization intensity of 47.4μC / cm 2 , breakdown field strength 728kV / cm, can release energy storage density up to 11.9J / cm3 , surpassing the releasable energy storage density of non-textured ceramic S1 and textured ceramic S4.

[0125] The lead-free energy storage ceramic materials obtained in Examples 3 and 4 and Comparative Examples 3 and 4 were analyzed: Figure 6 It can be seen that the texture degrees of S1, S2, S3 and S4 are 0.9%, 27.2%, 90.6% and 94.7% respectively. Figure 7 , Figure 8 It can be seen that, similarly, the non-textured ceramic S1 has the characteristics of high breakdown strength and low polarization strength, while the textured ceramic S4 has the opposite characteristics. Fig. 9 It can be seen that based on the same three-layer structure design, when using 0.88NaNbO 3 -0.12BiMg 0.5 Zr 0.5 O 3 In the multilayer ceramic S3 with components, a releasable energy storage density of up to 9.2 J / cm 3 .

[0126] The lead-free energy storage ceramic materials obtained in Examples 5 and 6 and Comparative Examples 5 and 6 were analyzed: Fig.10 It can be seen that the texture degrees of S1, S2, S3 and S4 are 0.1%, 9.9%, 96.4% and 94.2% respectively. Fig.11 , Fig.12 It can be seen that, similarly, the non-textured ceramic S1 has the characteristics of high breakdown strength and low polarization strength, while the textured ceramic S4 has the opposite characteristics. Fig.13 It can be seen that based on the three-layer structure design, when using (Ag 0.71 Bi 0.07 Sr 0.04 )(Nb 0.85 Ta 0.15 ) 3 In the multilayer ceramic S2 of the component, the purpose of having a releasable energy storage density better than S1 and S4 is also achieved.

[0127] This three-layer structural design idea of ​​stacking non-textured and textured ceramic layers with the same chemical composition can combine the advantages of non-textured and textured ceramics and give play to the synergistic effect of interface barrier to prepare lead-free high energy storage density laminated ceramic materials; and it can also be applied to other niobate-based ceramic materials, such as potassium niobate-based ceramics and lithium niobate-based ceramics. This is because this design strategy starts from the inverted relationship between dielectric constant and breakdown strength in any dielectric material, so the three-layer structural design idea is a universal strategy.

[0128] More importantly, compared with laminated ceramics with different chemical compositions, laminated ceramics with the same chemical composition are easier to co-fire.

[0129] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and implementation modes, and can be fully applicable to various fields suitable for the present invention. For those familiar with the art, for those of ordinary skill in the art, various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principle and spirit of the present invention. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.

Claims

1. A lead-free energy storage ceramic laminate material, characterized in that: The material is formed by sequentially stacking a lead-free energy storage ceramic with a textured structure and a lead-free energy storage ceramic with a non-textured structure.

2. The lead-free energy storage ceramic laminate material according to claim 1, characterized in that: The material includes at least three layers; when the lead-free energy storage ceramic with a textured structure is located in the middle layer, its two sides are lead-free energy storage ceramics with a non-textured structure; when the lead-free energy storage ceramic with a non-textured structure is located in the middle layer, its two sides are lead-free energy storage ceramics with a textured structure.

3. The lead-free energy storage ceramic laminate material according to claim 1, characterized in that: The lead-free energy storage ceramics include niobate-based, barium titanate-based, sodium bismuth titanate-based, and bismuth ferrite-based perovskite ceramics.

4. The lead-free energy storage ceramic laminate material according to claim 3, characterized in that: The niobate-based perovskite ceramics include sodium niobate, potassium niobate, lithium niobate, silver niobate, and potassium sodium niobate.

5. The method for preparing the lead-free energy storage ceramic laminate material according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1. Take carbonates or oxides of each element in the chemical formula of the lead-free energy storage ceramic and prepare ingredients according to the molar ratio of each element in the chemical formula; S2, subjecting the prepared raw materials to primary pulverizing ball milling, pre-calcination, secondary pulverizing ball milling or no secondary pulverizing ball milling, drying and sieving in sequence to obtain a basic powder; S3, mixing the base powder with a solvent, a dispersant, a plasticizer, and a binder to obtain a non-textured ceramic tape-casting slurry; mixing the base powder with a solvent, a dispersant, a plasticizer, a binder, and a template to obtain a textured ceramic tape-casting slurry; S4. The textured ceramic casting slurry and the non-textured ceramic casting slurry are respectively cast to obtain textured green ceramic sheets and non-textured green ceramic sheets, and the textured green ceramic sheets and non-textured green ceramic sheets are stacked in this order to obtain a ceramic green embryo, and then the binder is removed and sintered to obtain the lead-free energy storage ceramic laminate material.

6. The preparation method according to claim 5, characterized in that: In step S2, the ball milling medium for the primary and secondary pulverizing ball milling is anhydrous ethanol, and the ball milling speed is 250-350 r / min respectively; the time for the primary pulverizing ball milling is 8-14 h, and the time for the secondary pulverizing ball milling is 16-26 h; The pre-calcination is to increase the temperature to 750-950°C at 1-5°C / min and keep the temperature for 2.5-4h; The drying and screening is to dry the powder after the secondary powder making ball milling at a temperature of 75-85° C. and pass it through a 80-200 mesh sieve.

7. The preparation method according to claim 5, characterized in that: In step S3, the solvent is one or both of anhydrous ethanol and butanone; the dispersant is KD 1, the plasticizer is dibutyl phthalate, the binder is polyvinyl butyral, and the template is a NaNbO3 flaky microcrystalline template.

8. The preparation method according to claim 5, characterized in that: In step S3, when preparing the textured ceramic tape casting slurry and the non-textured ceramic tape casting slurry, the solvent accounts for 140-160wt% of the respective base powders, the dispersant accounts for 1.8-2.2wt% of the respective base powders, the plasticizer accounts for 5.8-6.2wt% of the respective base powders, and the binder accounts for 4.8-5.2wt% of the respective base powders; When preparing textured ceramic tape casting slurry, the template accounts for 4-5wt% of the basic powder.

9. The preparation method according to claim 5, characterized in that: In step S4, when the stacking is three layers, the stacking method is to sandwich the textured green ceramic sheet between the non-textured green ceramic sheets, and maintain the pressure at 4-8 MPa for 30-60 minutes to obtain a ceramic green embryo; or sandwich the non-textured green ceramic sheet between the textured green ceramic sheets, and maintain the pressure at 4-8 MPa for 30-60 minutes to obtain a ceramic green embryo.

10. The preparation method according to claim 5, characterized in that: In step S4, the debinding process parameters are: debinding temperature 620-700°C, insulation time 4-6h; the sintering process parameters are: sintering temperature 1095-1240°C, insulation time 3-4.5h.

Citation Information

Cited By

  • Anti-ferroelectric modified high-energy-storage BiFeO3-BaTiO3 ceramic and preparation method thereof

    CN119683984A

  • A high energy storage antiferroelectric modified BiFeO3-BaTiO3 ceramic and a preparation method thereof

    CN119683984B